Regulation of fucose and 1,2-propanediol utilization by Salmonella enterica serovar Typhimurium - Staib, Lena; Fuchs, Thilo M. (Frontiers in Microbiology, 2015)
After ingestion, Salmonella enterica serovar Typhimurium (S. Typhimurium) encounters a densely populated, competitive environment in the gastrointestinal tract. To escape nutrient limitation caused by the intestinal microbiota, this pathogen has acquired specific metabolic traits to use compounds that are not metabolized by the commensal bacteria. An example is the utilization of 1,2-propanediol (1,2-PD), a product of the fermentation of L-fucose, which is present in foods of herbal origin and is also a terminal sugar of gut mucins. Under anaerobic conditions and in the presence of tetrathionate, 1,2-PD can serve as an energy source for S. Typhimurium. Comprehensive database analysis revealed that the 1,2-PD and fucose utilization operons are present in all S. enterica serovars sequenced thus far. The operon, consisting of 21 genes, is expressed as a single polycistronic mRNA. As demonstrated here, 1,2-PD was formed and further used when S. Typhimurium strain 14028 was grown with L-fucose, and the gene fucA encoding L-fuculose-1-phosphate aldolase was required for this growth. Using promoter fusions, we monitored the expression of the propanediol utilization operon that was induced at very low concentrations of 1,2-PD and was inhibited by the presence of D-glucose.